2013
DOI: 10.1016/j.jacc.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Classification of the Instantaneous Wave-Free Ratio Is Equivalent to Fractional Flow Reserve and Is Not Improved With Adenosine Administration

Abstract: iFR and FFR had equivalent agreement with classification of coronary stenosis severity by HSR. Further reduction in resistance by the administration of adenosine did not improve diagnostic categorization, indicating that iFR can be used as an adenosine-free alternative to FFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
151
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 34 publications
15
151
1
1
Order By: Relevance
“…Our trial also provides clinical evidence that there is no significant advantage to the administration of a hyperemic agent -a finding consistent with results of studies in which iFR and FFR were compared with other reference standards. 13,14,19,20 Although evidence supporting the benefits of physiologically guided revascularization has accumulated over the past decade, adoption of this approach in clinical practice has lagged. There are many reasons for this, including equipment and drug costs, inadequate reimbursement, physician preferences, patient symptoms, and addi- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our trial also provides clinical evidence that there is no significant advantage to the administration of a hyperemic agent -a finding consistent with results of studies in which iFR and FFR were compared with other reference standards. 13,14,19,20 Although evidence supporting the benefits of physiologically guided revascularization has accumulated over the past decade, adoption of this approach in clinical practice has lagged. There are many reasons for this, including equipment and drug costs, inadequate reimbursement, physician preferences, patient symptoms, and addi- …”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have questioned the need for the administration of a vasodilator to assess stenosis severity. [12][13][14] In these studies, investigators found that in determining stenosis severity, FFR was not superior to the instantaneous wave-free ratio (iFR), a pressurederived index of stenosis severity that is not obtained with the administration of a vasodilator. We aimed to determine the efficacy and safety of an iFR-guided strategy versus an FFR-guided strategy for coronary revascularization.…”
mentioning
confidence: 99%
“…50 A second, larger study similarly assessed iFR and FFR against HSR in 120 stenoses. In that study, iFR was found to have a significant higher classification match than FFR (89% vs. 82%, P<0.01).…”
Section: Ifr Comparative Studies With Markers Of Ischemiamentioning
confidence: 99%
“…In CLARIFY, both iFR and FFR had equal diagnostic efficiency to match an ischemic classification with HSR (both 92%, with no significant difference between the 2 tests). 50 The CLARIFY study further addressed key questions brought by the cardiology community. One was whether iFR would be lower in the presence of adenosine, and whether the administration of adenosine over the wave-free period with further improve diagnostic categorization.…”
Section: Clarify Study: Assessing the Effect Of Hyperemia On The Wavementioning
confidence: 99%
“…[4][5][6][7] The instantaneous wave-free ratio (iFR) is a recently developed physiological index used to assess the severity of stenosis.The iFR is calculated by measuring the resting pressure gradient across a coronary lesion during the portion of diastole when microvascular resistance is low and stable. 8 Benefits of iFR include the ability to obtain an instantaneous lesion assessment without the need to administer a hyperemic agent, such as adenosine.…”
mentioning
confidence: 99%